Enhancing Accountability in Hajj Fund Governance Through Regulatory Impact Analysis and Value Chain Model - Achmad Iskandar Zulkarnain; Noer Azam Achsani; Mulya Siregar; Irfan Syauqi Beik (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2025)
This study analyzes the effectiveness of Indonesia's Hajj financial management regulations following the establishment of the Hajj Financial Management Agency (BPKH) under Law No. 34 of 2014. With increasing pilgrim demand exceeding available quotas, effective management of accumulated Hajj funds has become critical for ensuring pilgrim welfare and maintaining public trust. The research employs Value Chain Analysis and Regulatory Impact Assessment (RIA) methodologies through expert interviews and questionnaire surveys with key stakeholders. Value Chain Analysis identified nine key activities within BPKH's operations, while RIA evaluated policy impacts through systematic assessment of costs, benefits, and stakeholder perspectives. Findings reveal that BPKH's establishment significantly improved Hajj financial management with 100% expert consensus on enhanced transparency, efficiency, and accountability. However, the policy framework remains suboptimal due to service disparities among pilgrims, suboptimal investment returns, and incomplete institutional coordination. The study concludes that Law No. 34/2014 represents significant advancement in establishing clearer investment parameters and accountability frameworks, though digital transformation challenges persist. The research recommends strengthening investment risk management, expanding virtual account systems, and prioritizing comprehensive digital infrastructure development including IoT integration for operational monitoring, artificial intelligence for investment optimization, and blockchain technology for enhanced security while maintaining Sharia compliance.